Miscanthus sinensis ‘Gracillimus’ Shows Strong Submergence Tolerance Implying Its Potential Utilization in Construction of Ecological Ditches - Chunqiao Zhao; Ting Wu; Aoxiang Chang; Zhenyu Fan; Xiaona Li; Cui Li; Mei Zheng; Yu Sun; Xiuyun Wan; Jie Meng; Jing Zhang; Zebing Chen; et al. (Agronomy)
This study focused on three drought-tolerant grasses, namely Miscanthus sinensis ‘Gracillimus’ (Mis), Pennisetum alopecuroides ‘Ziguang’ (Pen), and Elytrigia repens (L.) Nevski ‘Jingcao No. 2′ (Ely), selected from nine species. Despite limited knowledge regarding their tolerance to submergence and responses to this stress, these three grasses were chosen for investigation. The three grass species were exposed to varying durations of submergence (0, 1, 3, 5, 7, 9, and 11 days) in a greenhouse setting. Subsequently, their growth characteristics, physiological traits, and nitrogen accumulation were evaluated. The study found that all three grass species exhibited flood tolerance, with Mis showing the strongest resistance. Under an 11-day flooding treatment, there was no significant trend in the above-ground biomass of Mis. Flooding significantly reduced the root-to-stem ratio, with Pen and Ely exhibiting more pronounced declines than Mis. The chlorophyll content in Mis decreased by 38%, compared to 41% in Pen and 60% in Ely. The root activity of the most affected species dropped by 88.6%, and nitrogen accumulation was inhibited with longer flooding durations. Pen’s nitrogen levels decreased significantly across treatments, while no significant changes were observed in Mis. Ely’s nitrogen assimilation initially increased until T4, after which it began to decline, reflecting similar trends in above-ground biomass. These findings suggest that flood tolerance is linked to nutrient uptake and photosynthetic capacity, highlighting Mis as the most suitable grass species for flood-prone areas and recommending its use in ecological ditch construction in China. This study provides material selection for the construction of ecological ditches.